Construct Rigidity: Keystone for Treating Pelvic Discontinuity. (3rd May 2017) - Martin, J. Ryan; Barrett, Ian; Sierra, Rafael J.; Lewallen, David G.; Berry, Daniel J.
Abstract : Background: Pelvic discontinuity is uncommon and presents the surgeon with complex reconstructive challenges. The objective of this study is to report the results of current strategies used in the treatment of pelvic discontinuity. Methods: We retrospectively analyzed prospectively collected data on 113 consecutive revision total hip arthroplasties performed for the treatment of unilateral pelvic discontinuity at a single institution. The study included 18 male and 95 female patients with a mean age of 63 years at the time of revision surgery. Preoperative, immediate postoperative, and latest follow-up radiographs were reviewed to assess healing of the discontinuity as well as acetabular component stability. Treatment modalities included an uncemented cup with a posterior column plate (50 hips; 44%), a cup-cage construct (27 hips; 24%), an antiprotrusio cage with or without a posterior column plate (26 hips; 23%), and an uncemented cup alone (10 hips; 9%). The average duration of follow-up for each of these types of surgical reconstruction was similar (range, 3.9 to 7.2 years). Results: Five-year revision-free survivorship of the implant was best with a cup-cage construct (100%) and worst with an uncemented cup with a posterior column plate (80%) and a cup alone (80%). Healing of the discontinuity was achieved in 50% of the hips with an uncemented cup alone, 74% of the hips with an uncemented cup and a posterior column plate, 74% of the hips with a cup-cage construct, and 88% of the hips with an antiprotrusio cage construct (91% of these hips when structural allograft was used). The overall complication rate was 26.5%. The average Harris hip score improved from 54 preoperatively to 69 postoperatively (95% confidence interval: 50 to 57 preoperatively and 65 to 72 postoperatively; p = 0.017). Conclusions: Improved survivorship and healing rates were seen in this series when a reconstruction cage was used as an adjunct to an uncemented cup (cup-cage) or in combination with structural allograft bone that bridged the discontinuity. Level of Evidence: TherapeuticLevel III . See Instructions for Authors for a complete description of levels of evidence.